1990
DOI: 10.1177/00220345900690110901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pd on the Clinical Performance of Amalgam

Abstract: The purpose of this study was to determine the effect of a small amount of Pd on the clinical performance of a high-copper spherical-particle dental amalgam. Two identical alloys, with and without 0.5% Pd, were investigated. The marginal fracture, surface texture, and surface luster of 193 clinical restorations were evaluated at one year, those of 182 at two years, and those of 144 at three years of service. In vitro corrosion tests of anodic polarization and constant potential coulometry were also conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Recent attempts to diminish Ni use in most industrial products have led to an increase in the use of different metal compounds for specific destinations such as the alloys used in orthopaedics, jewellery and dentistry [9]. For instance, the use of palladium (Pd) increased in the past 10 years [10] also due to the fact that dentistry alloys containing Pd appear more resistant to mechanical wearing effects [11,12]. Similarly, rhodium (Rh), which is primarily used as an alloying agent to harden platinum and Pd, it is now employed in electrical material because of its low electrical and contact resistance, in jewellery (platings of silver or white gold because of its silvery white colour), in optical instruments and dental prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…Recent attempts to diminish Ni use in most industrial products have led to an increase in the use of different metal compounds for specific destinations such as the alloys used in orthopaedics, jewellery and dentistry [9]. For instance, the use of palladium (Pd) increased in the past 10 years [10] also due to the fact that dentistry alloys containing Pd appear more resistant to mechanical wearing effects [11,12]. Similarly, rhodium (Rh), which is primarily used as an alloying agent to harden platinum and Pd, it is now employed in electrical material because of its low electrical and contact resistance, in jewellery (platings of silver or white gold because of its silvery white colour), in optical instruments and dental prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is convincing evidence that have shown that there is no difference in postoperative sensitivity in cases with and without bonding agents thus have seriously questioned the benefits of using bonding agents for sensitivity management. 24 Previously one study has shown an adhesive to be inferior to varnish in the seal it provides, 25 others have shown adhesives and varnishes to exhibit similar degrees of microleakage. 26,27 Our Study also is in line with one of the studies carried out in Agha Khan University, Karachi, showing that there was no difference in the postoperative sensitivity in the conventional and the bonded amalgam restorations in the Class I preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, data on local [8] and systemic toxicity [9] seemed to prove Pd safety. Due to its relatively cheap price, suitable processing qualities, and due to the fact that dentistry alloys containing Pd appear more resistant to mechanical wearing effects [10,11], exposure to Pd from use of dental appliances become more frequent in the population.…”
Section: Introductionmentioning
confidence: 99%